Mangrove vegetation structure in Southeast Brazil from phased array L-band synthetic aperture radar data - Souza Pereira, Francisca Rocha de; Kampel, Milton; Cunha-Lignon, Marilia [UNESP] (Spie-soc Photo-optical Instrumentation Engineers, 2016)
The potential use of phased array type L-band synthetic aperture radar (PALSAR) data for discriminating distinct physiographic mangrove types with different forest structure developments in a subtropical mangrove forest located in Cananeia on the Southern coast of Sao Paulo, Brazil, is investigated. The basin and fringe physiographic types and the structural development of mangrove vegetation were identified with the application of the Kruskal-Wallis statistical test to the SAR backscatter values of 10 incoherent attributes. The best results to separate basin to fringe types were obtained using copolarized HH, cross-polarized HV, and the biomass index (BMI). Mangrove structural parameters were also estimated using multiple linear regressions. BMI and canopy structure index were used as explanatory variables for canopy height, mean height, and mean diameter at breast height regression models, with significant R-2 = 0.69, 0.73, and 0.67, respectively. The current study indicates that SAR L-band images can be used as a tool to discriminate physiographic types and to characterize mangrove forests. The results are relevant considering the crescent availability of freely distributed SAR images that can be more utilized for analysis, monitoring, and conservation of the mangrove ecosystem. (C) The Authors. Published by SPIE under a Creative Commons Attribution 3.0 Unported License.
Keywords: mangrove; vegetation structure development; physiographic types; synthetic aperture radar; phased array type L-band synthetic aperture radar